The effect of differentiated learning on improving students' numeracy skills: an experimental study - Ilmi, Muhammad Bagus Nasrul (Indonesian Journal of Curriculum and Educational Technology Studies, 2023)
The Merdeka curriculum is designed to cater to individual student needs and interests, promoting differentiated learning that prioritises students' learning styles without imposing external pressures. However, despite recognising students' diverse characteristics, teachers often adhere to uniform teaching methods. This reluctance may be due to a lack of experience with independent learning systems, limited technological proficiency, and restricted access to educational resources. The objectives of this research include assessing the impact of differentiated learning on the numeracy skills of fifth-grade students at SDN Banyurip Ageng. The study employs quantitative methods within a pre-experimental design framework. The results indicate that differentiated learning positively affects numeracy skills in fifth-grade students at SDN Banyurip Ageng. Recommendations for educators include considering the adoption of differentiated learning models to enhance numeracy skills and emphasizing the importance of improving students' mathematical abilities. Abstrak Kurikulum Merdeka dirancang untuk memenuhi kebutuhan dan minat masing-masing siswa, mempromosikan pembelajaran berdiferensiasi yang mengutamakan gaya belajar siswa tanpa menimbulkan tekanan eksternal. Namun, meskipun menyadari karakteristik siswa yang beragam, guru sering kali tetap menggunakan metode pengajaran yang seragam. Keraguan ini mungkin disebabkan oleh kurangnya pengalaman dengan sistem pembelajaran mandiri, keterbatasan penguasaan teknologi, dan terbatasnya akses ke sumber daya pendidikan. Tujuan penelitian ini termasuk menilai dampak pembelajaran berdiferensiasi terhadap keterampilan numerasi siswa kelas lima di SDN Banyurip Ageng. Penelitian ini menggunakan metode kuantitatif dengan desain pra-eksperimental. Hasil penelitian menunjukkan bahwa pembelajaran berdiferensiasi memiliki efek positif terhadap keterampilan numerasi siswa kelas lima di SDN Banyurip Ageng. Rekomendasi untuk pendidik termasuk mempertimbangkan adopsi model pembelajaran berdiferensiasi untuk meningkatkan keterampilan numerasi, serta menekankan pentingnya peningkatan kemampuan matematika siswa.